KAPABILITAS BIROKRASI PEMERINTAH KOTA PEKANBARU DALAM MENGAWASI IZIN LINGKUNGAN HOTEL WISMA DAN PENGINAPAN DI KOTA PEKANBARU TAHUN 2013 (Studi Desentralisasi Politik, Administratif, dan Fiskal) - Oki Jumianto; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
The construction of hotels in the city of Pekanbaru in the last two years rose sharply, even the city government has issued a permit as many as 15 licenses good for a budget class hotels and 5 star hotels (five). Many of the buildings that stood in the city of Pekanbaru (Hotel) largely devoid Waste Installation (IPAL) in accordance with the provisions of Law number 32 Year About the Environmental Protection and live Management .IPAL is a device engineering equipment and equipment that processes / process liquids the rest of the industrial production process, so that the liquid is discharged into lingkungan.IPAL worth it is very beneficial for humans and other living organisms, other natara: Processing of domestic or industrial waste water, so that the water can be used again according to the needs of each, so that waste water which will be piped to the river is not polluted, and that the biota-organisms in the river is not dead.This study aims to determine the expected results of this study could be a starting point to conduct a deeper study of the implementation of decentralization, especially the readiness of local government structures in an effort to further streamline the supervision and feed into the overall development policy making. This study used qualitative methods and types of data collection using document review, interviews and observation, while the data processing procedures and data analysis using descriptive qualitative.It can be concluded, the City of Pekanbaru basing policy monitoring environmental permit hotels, guesthouses and inns on the mechanism of legislation exist, capability or ability of the administration of the City of Pekanbaru in monitoring environmental permit hotels, guesthouses and inns are considered adequate, the capabilities of the budget / fiscal support the environmental permit oversight hotels, guesthouses and inns are adequate and likely to get attention for environmental issues are fundamental and targeted directly to the public.Keywords: Capability, Decentralization Political, Administrative and Fiscal.